Stability of coalitional equilibria within repeated tax competition - Sonja Brangewitz; Sarah Brockhoff (Bielefeld University, Institute of Mathematical Economics (IMW), 2012)
This paper analyzes the stability of capital tax harmonization agreements in a stylized model where countries have formed coalitions which set a common tax rate in order to avoid the inefficient fully non-cooperative Nash equilibrium. In particular, for a given coalition structure we study to what extend the stability of tax agreements is affected by the coalitions that have formed. In our set-up, countries are symmetric, but coalitions can be of arbitrary size. We analyze stability by means of a repeated game setting employing simple trigger strategies and we allow a sub-coalition to deviate from the coalitional equilibrium. For a given form of punishment we are able to rank the stability of different coalition structures as long as the size of the largest coalition does not change. Our main results are: (1) singleton regions have the largest incentives to deviate, (2) the stability of cooperation depends on the degree of cooperative behavior ex-ante.
urn:nbn:de:0070-pub-26717212
Keywords: C71; C72; H71; H77; 330; capital tax competition; tax coordination; coalitional equilibria; repeated game; Kapitalertragsteuer; Steuerharmonisierung; Steuerwettbewerb; Nichtkooperatives Spiel; Koalition; Wiederholte Spiele; Theorie